1993
DOI: 10.1161/01.cir.88.5.2149
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking is associated with dose-related and potentially reversible impairment of endothelium-dependent dilation in healthy young adults.

Abstract: Cigarette smoking is associated with dose-related and potentially reversible impairment of endothelium-dependent arterial dilation in asymptomatic young adults, consistent with endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
821
8
57

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,390 publications
(931 citation statements)
references
References 39 publications
45
821
8
57
Order By: Relevance
“…This study was among the first in humans to demonstrate the important role of endothelial dysfunction early in the course of atherosclerosis. Similarly, abnormal vasomotion occurs in subjects with uncomplicated hypertension (71), diabetes (72)(73)(74)(75), cigarette smoking (76,77) and low levels of high density lipoprotein (78,79). Oxidized low density lipoprotein plays an important role in abnormal endothelial vasorelaxation, leukocyte adhesion and endothelin production (80)(81)(82)(83).…”
Section: Relationship Of Endothelial Function To Risk Factors and Thementioning
confidence: 99%
“…This study was among the first in humans to demonstrate the important role of endothelial dysfunction early in the course of atherosclerosis. Similarly, abnormal vasomotion occurs in subjects with uncomplicated hypertension (71), diabetes (72)(73)(74)(75), cigarette smoking (76,77) and low levels of high density lipoprotein (78,79). Oxidized low density lipoprotein plays an important role in abnormal endothelial vasorelaxation, leukocyte adhesion and endothelin production (80)(81)(82)(83).…”
Section: Relationship Of Endothelial Function To Risk Factors and Thementioning
confidence: 99%
“…The endothelium plays a central role in the control of vascular tone. 11 Impaired endothelium-dependent arterial dilatation has been demonstrated in both active smoking 12,13 and in prolonged exposure to environmental tobacco smoke. 14 Endothelial dysfunction has been implicated in the pathogenesis of coronary arterial spasm in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized LDL (OxLDL) in turn may induce endothelial expression of adhesion molecules, like intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) (Penn & Chisolm, 1994;Holvoet, 1999). Previous reports (Celermajer et al, 1993;Zeiher et al, 1995;Heitzer et al, 1996) have suggested that smoking induces endothelial dysfunction, which is regarded as an early event in atherogenesis.…”
Section: Introductionmentioning
confidence: 99%